Postinfarction left ventricular free wall rupture: a 17-year single-centre experience. (1st August 2017) - Formica, Francesco; Mariani, Serena; Singh, Gurmeet; D'Alessandro, Stefano; Messina, Luigi Amerigo; Jones, Norman; Bamodu, Oluwaseun Adebayo; Sangalli, Fabio; Paolini, Giovanni
Abstract: OBJECTIVES: Left ventricular free wall rupture (LVFWR) is a catastrophic complication following acute myocardial infarction with an estimated incidence of 0.2–7.6% and mortality can be as high as 60%. This study aimed to identify the risk factors for morbidity and mortality in patients affected by LVFWR. METHODS: This is a retrospective study of 35 patients who underwent surgery for LVFWR between January 2000 and December 2016 at our institution. RESULTS: The mean age of patients was 68.3 years. The in-hospital survival was 65.7% ( n  = 23), and 13% of survived patients presented with cardiac arrest. The following characteristics were associated with in-hospital mortality at univariable analysis: pre-existing hypertension ( P  = 0.02), need for inotropes ( P  = 0.02) and cardiac arrest ( P  < 0.0001) at presentation, cardiopulmonary resuscitation ( P  = 0.004), preoperative extracorporeal membrane oxygenation ( P  = 0.004), technique of LVFWR repair ( P  = 0.013), operation on extracorporeal membrane oxygenation ( P  = 0.005) and postoperative extracorporeal membrane oxygenation ( P  = 0.001). In the multivariable analysis, cardiac arrest at presentation was an independent predictor of in-hospital mortality (odds ratio 11.7, 95% confidence interval 2.352–59.063; P  = 0.003). The overall mean postoperative follow-up was 8.3 ± 1.3 years. Overall survival rates at 5 and 10 years were 53.2 ± 8.6% and 49.1 ± 8.9%, respectively. Among the survivors, only 6 (26.1%) patients died during follow-up with a 5-year and 10-year overall survival rate of 80.9 ± 8.7% and 74.7 ± 10%, respectively. CONCLUSIONS: These data suggest a trend towards long-term benefit in patients surviving high-risk surgery for LVFWR repair. Considering the high lethality of LVFWR, the urgency and complexity of the primary surgical intervention early diagnosis and prompt surgery play a key role in the management of this complication.